Three-Dimensional Bioprinting for Retinal Tissue Engineering - Kevin Y. Wu; Rahma Osman; Natalie Kearn; Ananda Kalevar (Biomimetics)
Three-dimensional bioprinting (3DP) is transforming the field of regenerative medicine by enabling the precise fabrication of complex tissues, including the retina, a highly specialized and anatomically complex tissue. This review provides an overview of 3DP’s principles, its multi-step process, and various bioprinting techniques, such as extrusion-, droplet-, and laser-based methods. Within the scope of biomimicry and biomimetics, emphasis is placed on how 3DP potentially enables the recreation of the retina’s natural cellular environment, structural complexity, and biomechanical properties. Focusing on retinal tissue engineering, we discuss the unique challenges posed by the retina’s layered structure, vascularization needs, and the complex interplay between its numerous cell types. Emphasis is placed on recent advancements in bioink formulations, designed to emulate retinal characteristics and improve cell viability, printability, and mechanical stability. In-depth analyses of bioinks, scaffold materials, and emerging technologies, such as microfluidics and organ-on-a-chip, highlight the potential of bioprinted models to replicate retinal disease states, facilitating drug development and testing. While challenges remain in achieving clinical translation—particularly in immune compatibility and long-term integration—continued innovations in bioinks and scaffolding are paving the way toward functional retinal constructs. We conclude with insights into future research directions, aiming to refine 3DP for personalized therapies and transformative applications in vision restoration.